Pemanfaatan Cengkeh dan Daun Salam pada berbagai Produk Kosmetik - kurniasari, fitri; Hayu W, Jena; Puspitasari, Ismi; Dwi A, Santi (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
Cloves are one of the richest sources of phenolic compounds such as eugenol, eugenol acetate and gallic acid and have great potential for pharmaceutical, cosmetic, food and agricultural applications. The aim of this community service activity is to provide knowledge regarding the benefits of cloves, which are applied in the form of cosmetic preparations, as well as providing training to partners so that their use is optimal and practical, and it is hoped that this can become a business opportunity. The solution proposed in this service activity is (1) providing knowledge about clove plants, (2) procuring materials in the form of medicinal plants for making preparations. (3) procurement of containers for the packaging process (4) conducting Good Manufacturing Practices (GMP) training to partners so that partners can make them independently. In service activities, the method used is an approach to the collaboration partner